2020
DOI: 10.1039/d0mt00143k
|View full text |Cite
|
Sign up to set email alerts
|

A copper complex formed with neurokinin B: binding stoichiometry, redox properties, self-assembly and cytotoxicity

Abstract: The tachykinin neuropeptide of neurokinin B (NKB) is a copper-binding amyloid peptide with important roles in the regulation of physiological functions and pathophysiological processes in the central and peripheral nervous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Furthermore, the lag phase for NKB(H 3 W) was longer than for NKB(H 3 F), which may reflect the larger size of Trp compared to Phe and the time required to arrange into pre-fibrillar oligomers that were large enough to allow ThT binding. Taken together with previous data showing that NKB(H 3 T) and NKB(H 3 A) mutants do not fibrillize [ 22 , 23 ], this experiment supports the idea that it is aromaticity at position 3 that is important for fibrillization, and not His specifically.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the lag phase for NKB(H 3 W) was longer than for NKB(H 3 F), which may reflect the larger size of Trp compared to Phe and the time required to arrange into pre-fibrillar oligomers that were large enough to allow ThT binding. Taken together with previous data showing that NKB(H 3 T) and NKB(H 3 A) mutants do not fibrillize [ 22 , 23 ], this experiment supports the idea that it is aromaticity at position 3 that is important for fibrillization, and not His specifically.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have shown that the copper disassembly of NKB fibrils can be monitored using ThT fluorescence. Disassembly leads to a loss of ThT fluorescence, which has been corroborated by analysis using atomic force microscopy [ 23 ] and electron microscopy [ 22 ]. Firstly, the wildtype NKB was analyzed.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, a standard 1 : 1 Cu(NKB) stoichiometry was proposed more recently on the basis of mass spectrometry experiments. 28 The latter result cannot be treated as definitive, however, because mass spectrometry of Cu(II)-peptide complexes is prone to a number of experimental issues which compromise the reliability of results. 29 In this study, we re-investigated the Cu(II) complexation by NKB using potentiometry, spectroscopic methods, and DFT calculations.…”
Section: Introductionmentioning
confidence: 99%